COMMUNITY VS GOVERNMENT: THE AGENCY OF CLIMATE DISCOURSE ON GREENPEACE SOUTHEAST ASIA WEBSITE - Arina Isti'anah; Hirmawan Wijanarka (Leksema: Jurnal Bahasa dan Sastra, 2025)
The climate discourse has been contested regarding its mitigation, mainly involving government and international organisations such as the UN. Hence, it is necessary to look for an alternative viewpoint that actively includes the community, or us, in the climate discourse. As a global non-governmental organisation, Greenpeace plays a crucial role in providing beneficial narratives that can broaden our perspectives on the worsening climate crisis and the state of our planet. This ecological discourse analysis (EDA) approach took data from articles on the climate crisis from the Greenpeace Southeast Asia website, henceforth abbreviated as GPSAW, and uploaded the corpus to Sketch Engine. By focusing on the words community and government (also their synonyms), this study examines the social actors based on theories by van Leeuwen (2008) and ecolinguistics by Stibbe (2015). Findings reveal that GPSAW articulates a beneficial discourse by involving the indigenous community and their ecological practices. While the government is also a significant player in the climate discourse, GPSAW actively engages the community as a crucial agent in mitigating the climate crisis. Even though communities are still represented as vulnerable actors, their active participation in voicing climate justice fosters the government’s roles as regulator and facilitator in climate mitigation. GPSAW is ecologically beneficial by locating communities as essential subjects in mitigating climate problems. This paper sheds a new light on the importance of narrating communities as crucial as the government and international organisations in climate discourse. The role of local communities is evident in their concrete actions in urging the government to create a more ecological policy.